PENGARUH PENGGUNAAN METODE PEMBELAJARAN INKUIRI DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X DI SMA N 1 PENENGAHAN TAHUN PELAJARAN 2013/2014 - Suratijo, Suratijo (Bioedukasi Jurnal Pendidikan Biologi, 2015)
The research has been done with the problem (1) What is the effect  of inquiry learning method toward the biology students achievement? (2) What is the effect of the relation between inquiry learning method and student activities toward biology students achievement? (3) Based on the high learning activities and the low learning activities, what is differences of biology students achievement uses inductive inquiry method and deductive inquiry method? Purpose of the research is to know (1) The effect of inquiry learning method toward the biology students achievement (2) The effect of relation between inquiry learning method and student activities toward biology students achievement (3) The differences of biology students achievement uses inductive inquiry method to the students who have a high learning activities (4)The differences of biology students achievement uses inductive inquiry method and deductive inquiry method who have low learning activities. The research uses the quantitative method with experiences approach 2 x 2 factorial design and descriptive analysis. Population in the research were the students  of the first grade of SMAN 1 Penengahan South Lampung, Academy years 2013 / 2014. Sampling uses the random sampling technique. The result of the research showed that (1) There is an inquiry learning method toward biology students achievement. That is seen in F-score = 6.31 > F-table = 4,20 (2) The effect of the relation between inquiry learning method and students activities toward biology students achievements. That is seen in F-score = 4,37 > Ftable = 4,20 (3) There is a real differences biology students achievement use inductive inquiry method and high learning activities, that is seen in F-score = 9,695 > F-table = 4,60  (4) There is a real differences biology students achievement use inductive inquiry method and low learning activities, that is seen in F-score = 1,579 < F-table = 4.60  Kata Kunci: metode pembelajaran inquiri, aktivitas belajar, hasil belajar